37 year snacking trends for US children 1977–2014. Issue 4 (15th May 2017) - Dunford, E. K.; Popkin, B. M.
Summary: Background: Previous studies have indicated that snacking is contributing to increased calorie intake of American children and that the energy density of snacks in US diets has increased in recent decades. Objective: Examine short‐term and long‐term trends in the energy density and food sources of snacks for US children from 1977 to 2014, and examine whether trends differ between socio‐demographic groups. Methods: We used data collected from eight nationally representative surveys of food intake in 49, 952 US children age 2–18 years, between 1977 and 2014. Overall patterns of snacking, trends in energy intake from snacking, trends in food and beverage sources and energy density of snacks across race‐ethnic, age, gender, education and income groups were examined. Results: In all socio‐demographic groups, there was a significant increase in per capita energy intake deriving from snacks from 1977 to 2014 ( P  < 0.01). Salty snack intake doubled over the study period, and sugar‐sweetened beverage intake decreased overall from 1977 to 2014 but increased in Non‐Hispanic Blacks. Non‐Hispanic Blacks had the largest increase in per capita intake from foods as a snack from 1977 to 2014. Children in the lowest poverty level and household education groups had more than 100% increase in calorie intake from snacks from 1977 to 2014. Conclusions: We found that snacking behaviour in the USA differs between race‐ethnic, household education, gender and income groups, yet snacking remains a significant component of children's diets and the foods consumed at these snacks are not the types of foods recommended by the US dietary guidelines.